Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2527/jas.2010-3330
|View full text |Cite
|
Sign up to set email alerts
|

Loci on Bos taurus chromosome 2 and Bos taurus chromosome 26 are linked with bovine respiratory disease and associated with persistent infection of bovine viral diarrhea virus1

Abstract: The objective of this study was to identify loci linked with bovine respiratory disease (BRD) and subsequently to determine if these same loci were associated with bovine viral diarrhea virus persistent infection (BVD-PI) in affected calves or their dams. A genome-wide linkage study using 312 microsatellites was conducted to identify loci linked with BRD in a Brahman × Hereford sire half-sib family. Disease incidence was recorded from birth to slaughter by daily monitoring. Linkage was suggestive for a QTL on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…However, the lower risk observed for Murray Greys in our study differs from that observed in a prior study involving a single feedlot (Cusack et al, 2007). Differences between breeds may be partly explained by genetic differences; genetic associations with BRD have been described in a genome-wide linkage study involving four half-sib families (Neibergs et al, 2011). Despite the difficulties in estimating heritabilities of complex diseases, low to modest heritabilities for BRD resistance have been reported (Mugglicockett et al, 1992;Snowder et al, 2006b).…”
Section: Discussioncontrasting
confidence: 55%
“…However, the lower risk observed for Murray Greys in our study differs from that observed in a prior study involving a single feedlot (Cusack et al, 2007). Differences between breeds may be partly explained by genetic differences; genetic associations with BRD have been described in a genome-wide linkage study involving four half-sib families (Neibergs et al, 2011). Despite the difficulties in estimating heritabilities of complex diseases, low to modest heritabilities for BRD resistance have been reported (Mugglicockett et al, 1992;Snowder et al, 2006b).…”
Section: Discussioncontrasting
confidence: 55%
“…Breed was identified as a very important risk factor with large population-level effects. Previous research provides evidence of an association between breed and BRD and plausible biological pathways have been proposed as genetic susceptibility has been shown to vary between breeds (Snowder et al, 2006;Neibergs et al, 2011). Similarly, prior research supports an adverse effect of lower induction weight (Sanderson et al, 2008;Reinhardt et al, 2009) and such a relationship is biologically plausible because lower induction weight animals may lack immunological maturity or may be low weight due to prior stressors relating to the plane of nutrition, parasitic or disease burden.…”
Section: Discussionmentioning
confidence: 93%
“…The economic losses are due to prenatal infections, infertility, abortions, congenital anomalies in calves, more neonatal deaths and persistently infected (PI) calves, which die due to mucosal disease. The incidence of BVD is usually unnoticed due to 70 to 90% of infections were in subclinical form (Neibergs et al, 2011). The BVDV was isolated from clinical samples for the first time in India by Mishra et al (2004).…”
Section: Bovine Viral Diarrhoea (Bvd)mentioning
confidence: 99%